KAPASITAS PEMERINTAHAN DESA DALAM IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 TENTANG DESA DI JAWA TENGAH - Suharto Suharto (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
This article describes the Capacity of the Village Government in the framework of implementing the 2014 Law Number 6 concerning Villages which is very important in determining its success. In this study aims to determine the extent of the capacity of the Village Government in implementing the Village Law. Looking at the current condition of the Village which is very heterogeneous, both quantity, quality or capacity and even the potential of natural resources and human resources are very varied, so in the context of implementing the Village Law it needs to be addressed or concern us, especially academics. The problems in this study are: "What is the capacity of the village government in the framework of implementing the Law Number 6 of 2014 concerning Villages?. Looking at the present condition of the village nationally, special steps are needed in the framework of implementing the Village Law. The parallel steps that must be considered and carried out in order to succeed the implementation of the Village Law include: First, the capacity level of the Village Government, namely the readiness of the Village Tools and Village Institutions (quantity and quality). Quantitatively, most villages currently do not have complete equipment as stipulated in PP 43/2014 article 61-article 64. Meanwhile, the available equipment capacity still needs to be improved. Second, the quality of the compilation of Village Development Planning documents (Village RPJM, Village RKP and Village APB). Based on PP 43/2014, paragraphs 114-115 and PP 60/2014 ps. 20, it is stated that the use of the Village Fund refers to the Village Medium Term Plan (RKPDes) and Village Government Work Plan (RKPDes). The implementation of the Village Law requires the capacity of the village government to master the technical and mechanism of managing trained and professional finance. With a number of issues, the current unprepared capacity makes feedback in efforts to improve the capacity of village financial management, together with all stakeholders (stakeholders), actors in the field, groups of care / volunteers and all village communities, because village funds must be able to promote the village and prosper villagers. Keywords: Village Government Capacity, Implementation of Village Law